Ejecutivo contra Legislativo: cobertura de un conflicto de poderes - Patriau Hildebrandt, Cesar Enrique (2020)
This work concentrates on the coverage that I made for the newspaper La República on the conflict between the Executive and the Congress. This political crisis led to the constitutional dissolution of the Legislative Branch decreed by the president, Martín Vizcarra, on September 30, 2019. Includes the main articles written in that period and develops the main lessons learned.